Digitalization of Data Management: Optimizing the Potential of Tawangsari Village, Sidoarjo - Ma'ruf, Aminudin; Rachmawati, Lucky; Wasil, Mohammad; Arisetyawan, Kukuh; Hutabarat, Ruth Eviana; Ramadhani, Clara Sinta Prameswari (Universitas Pahlawan Tuanku Tambusai, 2024)
The current data management system of Tawangsari Village is a manual. This creates obstacles for village officials and the community around them. Looking at the problem, it is necessary to digitize the data management system to tackle issues faced by the management of Tawangsari Village. The use of digital systems is believed to be able to handle the problem of information dissemination in Tawangsari village. The community service at Tawangsari Village aims to share the implementation of a digital data management system. In addition, the community service program is intended to enhance further collaboration between academia and the community. Based on security and ease of use, the community service program offers Google Forms as a tool for data management. Using Google Forms applications will bring changes from a conventional to a paperless culture. The community service program has unlocked the untapped potential of village data management to be more reliable